Baby crying acceptance in Portugal. (28th January 2011) - Martins, Tiago; De Magalhaes, Sergio Tenreiro
The baby's crying is his most important mean of communication. The crying monitoring performed by devices that have been developed does not ensure the complete safety of the child. It is necessary to join to these technological resources means of communicating the results to the responsible, which would involve the digital processing of information available from crying. The survey carried out enabled to understand the level of adoption, in the continental territory of Portugal, of a technology that will be able to do such digital processing. Technology acceptance model was used as the theoretical referential. The statistical analysis showed that there is a good probability of acceptance of such system.